Non-tetrapod sarcopterygian fossil material (Holoptychius sp., Rhizodontida indet., Dipnoi indet.) from Iveragh Peninsula (Ireland) - CT-Data, 3D-Models - Dupret, Vincent (Uppsala University, 2023)
The data set forms part of a study of fossil fish material from Southwest Ireland (Sarcopterygii: Dipnoi indet., Rhizodontida indet. och Holoptichius sp.; Givetian of the Iveragh Peninsula). The data consist of CTscan image stacks and subsequent working files (i.e. segmentation, visualisation files, STLs and 3D PDF files).

1. CT-scans datasets
At the Natural History Museum in London, the material was CT-scanned with a Nikon HMX ST 225 system, Nikon Metrology, Leuven, Belgium, with a tungsten reflection target. Detailed settings were adjusted for each specimen and are given in associated article (see "Material and Methods"). The specimen required stitching performed with an in-house NHM script written in Octave. In Oslo, at the Natural History Museum, University of Oslo, the scanning was carried out with a Nikon Metrology XT H 225 ST microfocus CT instrument at the Natural History Museum, University of Oslo, at 220 kV, 1245 µA, 4444 projections, 2 frames per projection,1 mm tin filter, Fast CT protocol (not minimising ring artefacts) and a voxel size of 23.9 µm. Detailed settings are given in in associated article.

2. Drishti and Mimics files (segmentation)

3. STL files

4. 3D pdfs
In Mimics, each individual structure corresponding to a mask was used to generate a high quality 3D object, itself transformed into an STL file. Each .stl file was then imported into Materialise 3-matic (v. 15.0) and Blender (v. 2.82). In 3matic, the following operations were applied to each .stl file to increase manageability while preserving accuracy: reduce number of triangles (geometrical error 0.1, preservation of surface contours) and smoothing (factor 0.1). A 3D pdf file was finally generated and can be open in Adobe Acrobat.

for the following specimens
a. NHMUK PV P 59686
Rhizodontida indet. (anterior coronoid with fang, one indet. facial bone), Dipnoi indet. (left lower jaw tooth plate), Bothriolepis dairbhrensis (indet anatomical element and Ml2, not analysed in the article). Segmentation in Mimics, treatment of STLS and 3d PDF exportation in 3-matic. The scale of the reference cube edges is 10 mm.

b. NMING:F35232
Holoptychius sp. (dermal scale). Segmentation in Mimics, treatment of STLS and 3d PDF exportation in 3-matic. The scale of the reference cube edges is 1 mm.

**LINKS TO PREVIOUSLY MENTIONED SOLUTIONS**
MATERIALISE MIMICS and 3-MATIC (segmentation, 3D modelling):
https://www.materialise.com/en/healthcare/mimics-innovation-suite

DRISHTI (3D visualisation):
https://github.com/nci/drishti
Ajay Limaye; Drishti: a volume exploration and presentation tool. Proc. SPIE 8506, Developments in X-Ray Tomography VIII, 85060X (October 17, 2012)

Datasetet är en del av en studie av fossilt fiskmaterial från sydvästra Irland (Sarcopterygii: Dipnoi indet., Rhizodontida indet. och Holoptychius sp.; Givetian på Iveragh-halvön). Data består av datortomografiska bildstaplar och efterföljande arbetsfiler (dvs. segmentering, visualiseringsfiler, STL-filer och 3D PDF-filer).

1. Dataset från datortomografi
På Londons Naturhistoriska Museum gjordes datortomografi på materialet med ett Nikon HMX ST 225-system (Nikon Metrology, Leuven, Belgien), utrustat med ett reflektionsmål av volfram. Detaljerade inställningar justerades för varje exemplar och finns angivna i den tillhörande artikeln (se "Material and Methods"). Exemplaren krävde sammanfogning med hjälp av ett särskilt framtaget NHM-skript skrivet i Octave.
Vid Naturhistorisk museum, Universitetet i Oslo, utfördes skanningen med ett Nikon Metrology XT H 225 ST mikrofokus CT-instrument vid Naturhistorisk museum, Universitetet i Oslo, med 220 kV, 245 µA, 4444 projektioner, 2 bilder per projektion, med 1 mm tennfilter, Fast CT protocol (icke minimering ringartefakter) och voxelupplösningen var 23.9 µm. Detaljerade inställningar finns angivna i den tillhörande artikeln.

2. Materialise Mimics och Drishti-filer (segmentering)

3. STL-filer

4. 3D PDF-filer
I Mimics användes varje enskild struktur som motsvarar en mask för att generera ett högkvalitativt 3D-objekt, som i sig omvandlades till en STL-fil. STL-filerna importerades sedan till Materialise 3-matic (v. 15.0) och Blender (v. 2.82). Varje STL-yta förenklades sedan och korrigerades med hjälp av följande funktioner: "reduce number of triangles" (geometrical error 0.1, preservation of surface contours) och "smoothing" (factor 0.1). Till slut genererades en 3D PDF-fil och den kan öppnas i Adobe Acrobat.”

för följande exemplar
a. NHMUK PV P 59686
Rhizodontida indet. (främre koronoid med huggtand, en indet. ansiktsben), Dipnoi indet. (vänster underkäke tandplatta), Bothriolepis dairbhrensis (indet anatomical element och Ml2, icke analyserat i artikeln). Segmentering i Mimics, behandling av STL-filer och 3D PDF-export i 3-matic och Blender. Referenskubens kanter är 10 mm.

b. NMING:F35232
Holoptychius sp. (dermal scale). Segmentering i Mimics, behandling av STL-filer och 3D PDF-export i 3-matic. Referenskubens kanter är 1 mm.


**LÄNKAR TILL ANVÄNDA VERKTYG**
MATERIALISE MIMICS and 3-MATIC (segmentering, 3D-modellering):
https://www.materialise.com/en/healthcare/mimics-innovation-suite

DRISHTI (3D-visualisering):
https://github.com/nci/drishti
Ajay Limaye; Drishti: a volume exploration and presentation tool. Proc. SPIE 8506, Developments in X-Ray Tomography VIII, 85060X (October 17, 2012)
Material av fossila kvastfeniga fiskar (Holoptychius sp., Rhizodontida indet., Dipnoi indet.) från Iveragh-halvön (Irland) - CT-data, 3D-modeller
Keywords: palaeogeography; paleogeografi; Devonian; devon; fossils; fossil; palaeozoology; paleozoologi; stratigraphy; stratigrafi; systematics; systematik (biologi); valentia island; valentia island; givetian; givetian; Rhizodontida; Porolepiformes; Dipnoi; Bothriolepis dairbhrensis; Holoptychius; Geology; Geologi; Zoology; Zoologi; Archaeology; Arkeologi; Other Natural Sciences; Annan naturvetenskap; Artefact; Artefact